Pharmacokinetics and Pharmacogenetics of Apixaban - A. V. Savinova; M. M. Petrova; N. A. Shnayder; E. N. Bochanova; R. F. Nasyrova (Рациональная фармакотерапия в кардиологии)
Apixaban is oral anticoagulant, it is widely used in prevention of stroke in non-valvular atrial fibrillation and treatment of deep vein thrombosis and pulmonary embolism. Its main mechanism of action is through reversible inhibition of factor Xa. It specifically binds and inhibits both free and bound factor Xa which ultimately results in reduction in the levels of thrombin formation. Apixaban is mainly metabolized by CYP3A4 with minor contributions from CYP1A2, CYP2C8, CYP2C9, CYP2C19 and CYP2J2 isoenzymes. Some of the major metabolic pathways of apixaban include o-demethylation, hydroxylation, and sulfation, with o-demethylapixabansulphate being the major metabolite. The aim of this review is analysis of associated researches of single nucleotide variants (SNV) of CYP3A5 and SULT1A1 genes and search for new candidate genes reflecting effectiveness and safety of apixaban. The search for full-text publications in Russian and English languages containing key words “apixaban”, “pharmacokinetics”, “effectiveness”, “safety” was carried out amongst literature of the past twenty years with the use of eLibrary, PubMed, Web of Science, OMIM data bases. Pharmacokinetics and pharmacogenetics of apixaban are considered in this review. The hypothesis about CYP и SULT1A enzymes influence on apixaban metabolism was examined. To date, numerous SNVs of the CYP3A5 and SULT1A1 genes have been identified, but their potential influence on pharmacokinetics apixaban in clinical practice needs to be further studies. The role of SNVs of other genes encoding beta-oxidation enzymes of apixaban (CYP1A2, CYP2C8, CYP2C9, CYP2C19, CYP2J2) and transporter proteins (ABCB1, ABCG2) in its efficacy and safety are not well understood, and ABCB1 and ABCG2 genes may be potential candidate genes for studies of the drug safety.